Increased intravascular platelet activity in metabolic syndrome patients, and its correction by simvastatin treatment - N. I. Gromnatsky; I. N. Medvedev; B. M. Golikov (Российский кардиологический журнал, 2004)
Simvastatin treatment in patients with arterial hypertension (AH) and metabolic syndrome (MS) corrects dyslipoproteinemia, peroxidation syndrome, and optimizes platelet homeostasis. Simvastatin inhibits increased intravascular platelet activity in vivo. For stable correction of metabolism and platelet homeostasis in patients with AH and MS, simvastatin therapy should be long-term. To reduce body weight and insulin resistance in patients with AH and MS, simvastatin could be combined with lifestyle modification.